1990
DOI: 10.1055/s-0038-1645199
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic Activation of Human Blood Coagulation Factors IX and X

Abstract: SummaryWe studied activation of human coagulation factors IX and X by factor VIIa in the presence of calcium ions, phospholipid (phosphatidylserine/phosphatidylcholine, 50/50, mol/mol) and purified tissue factor apoprotein. Activation of factor IX and factor X was found to occur without a measurable lag-phase and hence initial rates of factor IXa and factor Xa formation could be determined. Like previously observed for the activation of factor X, the activation of factor IX was saturable with respect to factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…Vm (Vmax) and Km values were calculated from Woolf plots as in Figs. 4 rophages (258 nM), but very similar to that obtained in a cell-free system (35,41,49). The Km of factor IX was 1.1-2.3-fold higher than the Km of factor X, whereas the Vmax of factor IX activation was 3-fold lower than that of factor X activation.…”
Section: Kinetic Parameters Of Extrinsic Activation Of Factor X and Fsupporting
confidence: 78%
See 2 more Smart Citations
“…Vm (Vmax) and Km values were calculated from Woolf plots as in Figs. 4 rophages (258 nM), but very similar to that obtained in a cell-free system (35,41,49). The Km of factor IX was 1.1-2.3-fold higher than the Km of factor X, whereas the Vmax of factor IX activation was 3-fold lower than that of factor X activation.…”
Section: Kinetic Parameters Of Extrinsic Activation Of Factor X and Fsupporting
confidence: 78%
“…Data for the cell-free system are taken from ref. 35; these reactions were performed at 0.4-0.6 nM tissue factor apoprotein, 25 µM phospholipid (50 mol% phosphatidylserine: 50 mol% phosphatidylcholine) and 0.01 nM factor Vila. Vm (Vmax) and Km values were calculated from Woolf plots as in Figs.…”
Section: Kinetic Parameters Of Extrinsic Activation Of Factor X and Fmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads to the conclusion that additional VKDP at elevated concentrations have pronounced inhibitory effect on thrombin generation. Data published from several laboratories have established that FIX inhibits FX activation by the FVIIa/TF complex due to the competition of these two zymogens for the same complex enzyme [23,38–42]. In this study a substantial increase in the duration of the initiation phase was observed when an elevated concentration of FIX was present in a reaction with phospholipids in the absence of FXI.…”
Section: Discussionmentioning
confidence: 55%
“…As in the experimental system (15), the TF-VIIa complex is assumed to be fully formed at the start of the experiment, so descriptions of the binding of VII(a) to TF and the activation of VII are not included. The TF-VIIa complex activates both IX (17) and X (18). IXa forms complexes with VIII (19) or VIIIa (20); the VIIIa-IXa (tenase) complex also activates X (21,22).…”
Section: Resultsmentioning
confidence: 99%